POTENTIAL BENEFITS OF LEARNING ENGLISH USING LATEST APPLICATIONS AS LEARNING INNOVATIONS FOR STUDENTS ENGLISH PROFICIENCY - Ninuk Wihartami; Ine Rahayu Purnamaningsih (IKIP Siliwangi, 2022)
Smartphone technological developments provide possibilities for various social media applications to play an important role in today’s society. TikTok has become a favorite among almost all Indonesians as one of the most recent popular social media applications. As a result, the TikTok application is advised to be used wisely in order to benefit and have a positive impact in the world of education. Previous research, explains the TikTok application’s limited use for learning activities, particularly English. Therefore, this study aims to explore the potential benefits of the TikTok application for learning English for students' English proficiency. This study uses a qualitative approach to find out the benefits of the TikTok application as an innovation in learning media. 16 English Language Education students at Singaperbangsa Karawang University voluntarily took part in a quantitative survey research, using an online questionnaire as a research instrument. The findings show that there are four potential benefits to using the TikTok. The benefits found include time and location savings, educational content on the TikTok application is very informative, content on the TikTok application is easy to understand when learning English, and TikTok content can grow and increase students in learning English. Furthermore, students stated that the TikTok application could be used for learning English in the classroom. Keywords: Tiktok Application, Learning English, Innovation Media